Lower urinary tract dysfunction in Multiple Sclerosis, Updates (ORP-31) - Shekoofeh Alaie (Neurology Letters, 2023)
MS  is a leading cause of LUT dysfunction in neurological i  patients and LUT symptoms are  reported in an average 8 yrs after the diagnosis of MS. LUT dysfunction is simply and  traditionally  divided  into  Storage  failure ,  emptying failure  and combination of  these two. Today   ICS  classification  is based on UDS  characteristics  measured  for  both  storage and emptying  phases. The management of LUT dysfunction is  highly personalized  and  focuses, primarily, on the improvement of patients’ symptoms and QoL and secondarily, on the preservation of the upper urinary tract and avoidance of urological complications (e.g., urinary tract infections, bladder stones, and  renal impairment . First-line treatments include fluid management, pelvic floor muscle training (PFMT), and medical therapies (e.g., antimuscarinic agents alone or in combination with B3 receptor agonists ). second-line treatments include BTX-A injections, intravesical therapies, invasive and non-invasive neuromodulation, and catheterization. Surgery may be indicated in select cases. First-line management can be initiated in neurological practice, but early referral to a urology service should be considered in certain situations, specially  if red flags are present.